Effect of casein phosphopeptide-amorphous calcium phosphate and erbium:Yttrium–Aluminium–Garnet laser on shear bond strength to demineralized dentin - Moosavi, Horieh; Nemati-Karimooy, Atefeh (European Journal of General Dentistry, 2020)
Objective: The aim of this in vitro study was to investigate the effect of casein phosphopeptide–amorphous calcium phosphate (CPP-ACP)-containing paste (MI Paste) and erbium:yttrium–aluminum–garnet (Er:YAG) laser radiation on the shear bond strength (SBS) of an etch-and-rinse (E and R) adhesives to demineralized dentin. Materials and Methods: Forty-eight carries-free human dentin surfaces were prepared and demineralized using acidic solutions. Then, the samples were randomly divided into four groups (n = 12) receiving different surface treatments. Group A (control group): no additional treatment, Group B: 3 min application of a CPP-ACP-containing cream (MI Paste), Group C: irradiation of Er:YAG laser, and Group D: irradiation of Er:YAG laser combined with 3 min application of CPP-ACP-containing cream (MI paste). Then, a composite cylinder (Filtek™ Ultimate, 3M ESPE) bonded to the surfaces using E and R adhesives (single bond) and the SBS was measured. The SBS data were analyzed using the one-way analysis of variance test followed by Tukey post hoc by SPSS software. Results: The highest SBS to demineralized dentin was observed after the application of CPP-ACP-containing paste (MI paste) without laser radiation (17.14 ± 2.07). The second highest SBS value showed in control group (11.21 ± 1.65) in which demineralized dentin received no additional treatment. However, the application of MI paste combined with Er:YAG laser irradiation resulted in the higher SBS (8.23 ± 1.02) than laser irradiation alone (5.26 ± 1.02), even though both were lower than control group. Conclusions: The application of CPP-ACP-containing paste (MI paste) could increase the SBS of E and R adhesives to demineralized dentin. Furthermore, laser irradiation with and without CPP-ACP application has an adverse effect on SBS.
Keywords: Casein phosphopeptide–amorphous calcium phosphate; demineralized dentin; erbium:yttrium–aluminum–garnet laser; etch-and-rinse adhesives; shear bond strength